Dipeptidyl Peptidase-4 Inhibitors and the Risk of Pancreatitis in Patients with Type 2 Diabetes Mellitus: A Population-Based Cohort Study - Young-Gun Kim; Seirhan Kim; Seung Jin Han; Dae Jung Kim; Kwan-Woo Lee; Hae Jin Kim (Journal of Diabetes Research)
Background. Information on the risk of acute pancreatitis in patients receiving dipeptidyl-peptidase IV inhibitors (DPP-4i) is limited and controversial. One study suggested that the differences in findings between these meta-analyses were attributed to whether they included large randomized control trials with cardiovascular outcomes or not. The aim of our study was to determine whether the use of DPP-4i increases the risk of acute pancreatitis compared with sulfonylurea (SU) and whether the risk is higher in patients with underlying cardiovascular disease (CVD). Methods. A population-based cohort study was performed using Korean National Health Insurance Service-National Sample Cohort data. We included 33,395 new users of SU and DPP-4i from 1 January 2008 to 31 December 2015. SU-treated patients and DPP-4i-treated patients were matched by 1 : 1 propensity score matching. We used Kaplan–Meier curves and Cox proportional hazards regression analysis to calculate the risk of acute pancreatitis. Results. The hazard ratio (HR) of hospitalization for acute pancreatitis was 0.642 (95% confidence interval (CI): 0.535–0.771) in DPP-4i-treated patients compared with SU-treated patients. The HR of DPP-4i use was also lower than that of SU use in patients without underlying CVD (HR: 0.591; 95% CI: 0.476–0.735) but not in patients with underlying CVD (HR: 0.727; 95% CI: 0.527–1.003). Conclusion. Our findings suggest that DPP-4i is less likely to cause drug-induced pancreatitis than SU. This finding was not evident in patients with CVD, but DPP-4i was not more likely to induce pancreatitis in these patients than SU was.